2018
DOI: 10.1016/j.micres.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of apple and blackcurrant microbiota in Lithuania and the Czech Republic

Abstract: The microbial assemblies on the surface of plants correlate with specific climatic features, suggesting a direct link between environmental conditions and microbial inhabitation patterns. At the same time however, microbial communities demonstrate distinct profiles depending on the plant species and region of origin. In this study, we report Next Generation Sequencing-based metagenomic analysis of microbial communities associated with apple and blackcurrant fruits harvested from Lithuania and the Czech Republi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 49 publications
9
28
0
Order By: Relevance
“…Changes in the planting regime alter microbial habitat and diversity, affect functional traits [22]. Comprehensive next-generation sequencing-based (NGS) microbiome analysis accomplished on several fruits and berries-such as apples, blackcurrants, grapes, olives, strawberries, oranges, etc.-is mainly focused on plant-conditioned prevalence [23][24][25][26][27][28]. The biogeographic distribution of microbiota communities has been revealed on apple, blackcurrant, and grape [21,28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the planting regime alter microbial habitat and diversity, affect functional traits [22]. Comprehensive next-generation sequencing-based (NGS) microbiome analysis accomplished on several fruits and berries-such as apples, blackcurrants, grapes, olives, strawberries, oranges, etc.-is mainly focused on plant-conditioned prevalence [23][24][25][26][27][28]. The biogeographic distribution of microbiota communities has been revealed on apple, blackcurrant, and grape [21,28].…”
mentioning
confidence: 99%
“…Comprehensive next-generation sequencing-based (NGS) microbiome analysis accomplished on several fruits and berries-such as apples, blackcurrants, grapes, olives, strawberries, oranges, etc.-is mainly focused on plant-conditioned prevalence [23][24][25][26][27][28]. The biogeographic distribution of microbiota communities has been revealed on apple, blackcurrant, and grape [21,28]. The effect of the ripening stage on the development of the microbial population was investigated in grapes, mango, nectarines and plums [8,[29][30][31].…”
mentioning
confidence: 99%
“…The plant habitat is a dynamic environment where many factors can affect the structure of the microbial community [4,30]. Previous studies have shown that different plant organs host a different fungal community [18,27,32]. This was verified using a survey that found fungal community structures differed significantly among five organs, since each organ forms a distinctive microenvironment.…”
Section: Discussionmentioning
confidence: 92%
“…Dothideomycetes has also been reported as the largest group in Pinus halepensis Mill. [45], Lycopodium annotinum L. and Lycopodium clavatum L. [46], as well as blackcurrant berries in Lithuania [32]. Members of Dothideomycetes include several plant pathogens and the majority are found to be endophytes, or saprobes growing on woody debris, decaying leaves or dung [19,46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation